2022
DOI: 10.2209/tdcpublication.2021-0016
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Availability of Domiciliary Dental Care under 16-km Rule

Abstract: In Japan, domiciliary care fees are only covered by the public health insurance system if the clinic concerned is located within 16 km of the patient's residence. This nationwide rule does not take local conditions into account and therefore may not be appropriate. The goal of the present study was to assess the current state of domiciliary dental care nationwide in view of this restriction to clarify the current situation and any inherent problems. Six dental institutions providing domiciliary dental care wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The cost of dental care was strongly influenced by factors such as geographic region, age, income per capita, prevalence of government assistance programs, frequency of inoffice complete dentures, and frequency of home visits [40]. The travel time variable was a better parameter than the distance traveled by the caregiver [14]. Many users of this program reported that the cost of treatment was the main concern of patients joining the DDC program [5,33,40].…”
Section: 4mentioning
confidence: 99%
“…The cost of dental care was strongly influenced by factors such as geographic region, age, income per capita, prevalence of government assistance programs, frequency of inoffice complete dentures, and frequency of home visits [40]. The travel time variable was a better parameter than the distance traveled by the caregiver [14]. Many users of this program reported that the cost of treatment was the main concern of patients joining the DDC program [5,33,40].…”
Section: 4mentioning
confidence: 99%